China’s Afghan Policy: De Facto Recognition of The Taliban Regime - Umami, Liza; Cipto, Bambang (Intermestic: Journal of International Studies, 2023)
This study aims to investigate China’s proactive stance toward developing tight ties with the Taliban regime. The author applies external-internal setting theory to examine China’s reasons for not carrying out Government Recognition to Taliban regime along with rational choice theory to emphasize why the choice to recognize the Taliban only as a de facto is the best solution for China’s current national interests. To study China’s foreign policy, a qualitative-explanatory method with a deductive method is used. After analyzing China’s concerns about Xinjiang instability as one of the “5 Poisons” and China’s security projects and investments in Afghanistan and the South and Central Asia region due to the Taliban’s weak legitimacy, this paper concludes that the recognition of Taliban regime is not a priority agenda at this time. China prioritizes regional cooperation and international support due to Afghanistan-based terrorism. Keywords: Foreign Policy, China, Taliban, Afghanistan, De Facto Recognition